Antioxidant activity, total phenolic and flavonoid content from leaves and seed extracts of Hevea brasiliensis clone / Wan Zuraida Wan Mohd Zain ... [et al.] - Wan Mohd Zain, Wan Zuraida; Ramli, Nur Nadia; Jusoh, Samsiah; Hamid, Nur' Amira (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Rubber tree or Hevea brasiliensis is an industrial crop from Euphorbiaceae family that grows in tropical climates and commonly known as an important economical commodity to Malaysia. However, there is a little information available on its phytochemicals in each part of rubber tree as well as their antioxidant activity. The aims of this study are to determine the extraction yield of different clone of rubber tree as well as to determine the antioxidant activity, total phenolic and flavonoid content from leaves and seeds extracts. The leaves and seeds extraction process were optimized by varying different parameter's such as drying temperature, types of solvent used and temperature of extraction. The drying process was done at temperature of 70℃ for 24 hours. The dried samples were macerated with methanol and the extract was concentrated using rotary evaporator at 60℃. The highest percentage of inhibition was based on the weight of dried plant materials. The determination of antioxidant was assessed by using the DPPH assay method. The total phenolic and flavonoid content was determined by using Folin- Ciocalteau assay and aluminium chloride colorimetric assay respectively. From this study, the result indicates that, the highest extraction yield was seeds extract (29.77%) from clone RRIM 2020. The highest amount of antioxidant was (79.16) from clone RRIM 2025. Therefore, the highest amount for total phenolic and flavonoid content were clone RRIM 2020 (0.020) and RRIM 3001 (0.200) respectively. As a conclusion, it showed that each clone gives a different result on each of the analysis. The result will be benefit to others for their reference in order to produce the product.